2020
DOI: 10.3390/w12051419
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal Efficiency and Growth of Watercress (Nasturtium officinale) under Different Harvesting Regimes in Integrated Recirculating Aquaponic Systems for Rearing Common Carp (Cyprinus carpio L.)

Abstract: The harvesting of plant biomass is usually implemented as an effective tool for plant management and removing the nutrients absorbed in plant tissues. Here, the influence of harvesting different biomasses (50%, 33%, 25%, and 0% (no harvest)) of watercress (Nasturtium officinale) was investigated in integrated recirculating aquaponic systems (IRASs) for rearing common carp (Cyprinus carpio). Twelve independent IRASs were designed (4 × 3); each system consisted of a fish rearing tank, a waste collection tank, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…The current study also agreed with [9] that the ammonia concentration is low due to the ability of rice to consume ammonia, which was confirmed by [18]. [16] observed a decrease in the average ammonia concentrations in all transactions until the end of the experiment. The ammonia values were (0.378, 0.867, 0.771, 0.816) respectively.…”
Section: Water Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…The current study also agreed with [9] that the ammonia concentration is low due to the ability of rice to consume ammonia, which was confirmed by [18]. [16] observed a decrease in the average ammonia concentrations in all transactions until the end of the experiment. The ammonia values were (0.378, 0.867, 0.771, 0.816) respectively.…”
Section: Water Propertiessupporting
confidence: 91%
“…Oxygen diffuses in water in two ways, the most important of which is diffusion from atmospheric air and then metabolism, where the product of the process of extracting plants for carbon dioxide is the production of O 2 . The results of [16] showed that the O2 values in all coefficients were (8.16, 8.19, 8.24, 8.34) at (0%-25%-33%-50%) respectively. [17] stated that the percentage of dissolved oxygen inside the closed water system between 8.5-10.1 mg/L due to the low temperature, the oxygen portability higher during the experiment period, which is an appropriate ratio for growth and breeding of common carp fish.…”
Section: Water Propertiesmentioning
confidence: 99%
“…The study discovered that biweekly gathering compared with fewer than 25 percent of the mass of the developing arugula is advised for nitrification and the economic progress of both the arugula and the carp in aquaponics (Irhayyim et al 2020).…”
Section: Automationmentioning
confidence: 99%
“…Currently, nitrogen is the most studied nutrient element, and pH is the key factor affecting nutrient circulation. "growth" is the hub of cluster 4 (blue) which mainly discusses aquaponics production [22][23][24]. A series of requirements for system output were proposed, such as growth, yield, quality, and sustainability.…”
Section: Hot Issue and Research Area Of Aquaponicsmentioning
confidence: 99%
“…Several researchers summarized the challenge of aquaponics development, there are two major issues need to be solved urgently: (1) The operation and maintenance of aquaponics need more strategy [39] because insecticides and antibiotics cannot be used in aquaponics, it is difficult to prevent fish and plants from disease and pests [14]. In addition, plants have different requirements for nutrients at different growth stages [49], and it has not been resolved how to integrate the hydroponic subsystems with the aquaculture one to maximize nutrient utilization efficiency, so more culture strategies are urgently needed [23]. (2) Low social recognition: for aquaponics commercialization, high investment [34] causes high price of aquaponics products, and there is currently no policy to subsidize the initial investment in the construction of aquaponics.…”
Section: Future Of Aquaponics Researchmentioning
confidence: 99%